NHC Organocatalysis in D2O for the Highly Diastereoselective Synthesis of Deuterated Spiropyran Analogues. Issue 9 (1st March 2021) - Suresh, Pavithira; Thamotharan, Subbiah; Selva Ganesan, Subramaniapillai
Abstract: Metal‐free N‐heterocyclic carbene (NHC) organocatalysis in D2 O medium was elegantly utilised for the synthesis of highly diastereoselective deuterated spiropyran derivatives. Selective deuteration was exclusively achieved on the C5 carbon atom of the pyran ring. Quantum chemical calculations were performed to prove the preferential formation of a single diastereomer from the possible four diastereomers. The scope of NHC organocatalysis in D2 O was also extended for the synthesis of deuterated spirooxindole derivative. Abstract : Metal‐free NHC catalysis in D2 O solvent was utilized in the synthesis of deuterated spiropyran analogues. The reaction was found to be highly diastereoselective and all the products were obtained in moderate to good yields. Quantum chemical calculations support the formation of the major diastereomer. The position of deuteration was confirmed by comparing the 1 H‐NMR of the deuterated molecule with the non‐deuterated molecule.